P262 ULTRASOUND–ASSISTED THROMBOLYSIS OF HIGH RISK AND INTERMEDIATE–HIGH RISK PULMONARY EMBOLISM: A MULTICENTRE REAL WORLD EXPERIENCE IN LOMBARDY REGION. (18th May 2022) - Russo, F; Cianfanelli, L; Galli, M; Chizzola, G; Bossi, I; Chieffo, A; Montorfano, M
Abstract: Introduction: Acute pulmonary embolism (PE) is associated with high morbidity and mortality rate. Catheter–directed treatments (CDTs) seem a therapeutical option in case of sistemic thrombolysis (ST) contraindication or failure. Ultrasound–assisted thrombolysis (USAT) allows low–dose thrombolytic loco–regional infusion facilitated by ultrasounds. Methods and Results: A multicentre retrospective observational cohort study was conducted among 4 Cardiovascular Interventional Centres in Lombardy Region to evaluate safety and efficacy of USAT in high risk and intermediate–high risk PE patients presenting with contraindications to ST. Patients at high risk were included in case of USAT because of ST contraindications. Patients at intermediate–high risk were included in case of rescue USAT. Loco–regional thrombolysis was performed using rTPA. Procedural success was defined as successful catheters' deployment in pulmonary arteries and patient survival during the procedure. Bleeding were defined according to BARC criteria. Echocardiographic evaluation to determine the prevalence of right ventricular (RV) dysfunction and pulmonary hypertension was performed at presentation, discharge and follow–up. Between 2011 and 2021, 109 patients were included. 21.1% presented with high risk PE, the remaining 78.9% with intermediate–high risk. Procedural success was obtained in 99.1% of the cases; major bleedings occurred in 9.2%, minor bleedings in 11.9% and vascular complications in 7.3% of the patients. 91.7% of patients were alive at discharge. In–hospital all–cause mortality was higher in high risk patients (26.1% vs 3.5%; p = 0.003) that showed a steep decline in survival as compared to intermediate–high risk patients that constantly maintained a high survival rate throughout the observation period. At six–months follow–up 3 patients in intermediate–high risk group died so that the overall mortality remains higher in high risk patients (26.1% vs 7%; p = 0.018). No re–hospitalization for recurrent PE at six–months occurred. Prevalence of RV dysfunction and pulmonary hypertension significantly decreased from hospital admission to discharge and to six–months follow–up (p–value <0.0001 for all comparisons). Conclusions: Our experience shows good short and mid–term outcomes in USAT in high risk and intermediate–high risk PE patients with contraindications to ST, suggesting that it might be considered in a neglected subset of patients with no alternative therapeutical options.